A Study of Fossilization in Chinese College Students’ English Learning - Xinguang, SHAO (Advances in Social Sciences Research Journal, 2015)
The study aims to investigate the causes of fossilization in Chinese college students’ English learning with the help of questionnaires and interview with some subjects. The results show that some factors may cause the fossilization of many Chinese college students’ English. They include the students’ lack of interest and strategies in English learning, English teachers’ lack of good teaching methods, the negative transfer of the students’ mother Language and some problems in English textbooks and Chinese education system. Both the students and their English teachers should make great efforts to find useful strategies to overcome the fossilization.